2016
DOI: 10.1111/1462-2920.13371
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of aquatic marine fungi across the western Arctic and sub‐arctic

Abstract: Fungi are important parasites of primary producers and nutrient cyclers in aquatic ecosystems. In the Pacific-Arctic domain, fungal parasitism is linked to light intensities and algal stress that can elevate disease incidence on algae and reduce diatom concentrations. Fungi are vastly understudied in the marine realm and knowledge of their function is constrained by the current understanding of fungal distribution and drivers on global scales. To investigate the spatial distribution of fungi in the western Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 42 publications
8
75
0
Order By: Relevance
“…), the Artic and Subartic Sea (Hassett et al. ). This cluster, constitutes a novel clade (SW‐I) within Lobulomycetales.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), the Artic and Subartic Sea (Hassett et al. ). This cluster, constitutes a novel clade (SW‐I) within Lobulomycetales.…”
Section: Resultsmentioning
confidence: 99%
“…) and Arctic sea ice (Hassett et al. ) in a separate, novel clade, sister to the order Lobulomycetales (Simmons et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chytrids). These true fungi are commonly found in freshwater, brackish and marine pelagic environments (Lepère et al, 2016;Hassett et al, 2017;Maier and Peterson, 2017). Chytrid fungi display a characteristic free-living life stage as flagellated zoospores.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, chytrid infections of marine microalgae and cyanobacteria and in particular diatoms (Bacillariophyceae), have only been considered in recent years (e.g., [5,6,7,8]). Although latest molecular surveys have shown that chytrids are ubiquitous and common in marine environments around the globe (e.g., [9,10,11,12]), the biology and eco-evolutionary role of marine aquatic parasites in general, and chytrids in particular remain largely unstudied.…”
Section: Introductionmentioning
confidence: 99%